MENINGKATKAN PENGUASAAN KOSAKATA BAHASA INGGRIS UNTUK MURID PENDIDIKAN ANAK USIA DINI MELALUI BUKU CERITA BERGAMBAR PADA KELOMPOK B DI TK SUCI CASTELLIA - Abdullah, Suci C. N.; Tulung, Golda J.; Rambing, Rosalina (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2020)
ABSTRACTThe research was conducted due to students' low ability in mastering English vocabulary. This research aimed at finding out how the use of picture storybook could improve the students' mastery at Group B of TK Suci Castellia Manado. This research used classroom action research. It was done in two cyles, which consisted of two meetings for each cycle. The researcher did the research based on the procedures of classroom action research which are planning, action, observation, and reflection. The data were obtained from observations, an interview, documentation and tests (pre-test and post-test). It was found that the use of picture storybook on the first cycle showed a slow increase in the students' ability to master English vocabulary. In the second cycle, some improvements were made during the learning process. In this second cycle, English vocabulary at Group B students increased with the use of picture storybooks. The second cycle showed that the mastery of English vocabulary tended to increase. From both cycles, it indicates that the use of picture storybook can improve students' vocabulary mastery at Group B of TK Suci Castellia Manado. Keywords : English Vocabulary, Picture Storybook, Early Childhood Education